2006
DOI: 10.1146/annurev.energy.31.042606.085844
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity Conservation Planning Tools: Present Status and Challenges for the Future

Abstract: ■ Abstract Species extinctions and the deterioration of other biodiversity features worldwide have led to the adoption of systematic conservation planning in many regions of the world. As a consequence, various software tools for conservation planning have been developed over the past twenty years. These tools implement algorithms designed to identify conservation area networks for the representation and persistence of biodiversity features. Budgetary, ethical, and other sociopolitical constraints dictate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
379
0
16

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(397 citation statements)
references
References 205 publications
(234 reference statements)
2
379
0
16
Order By: Relevance
“…As highlighted in Egoh et al (2007Egoh et al ( , 2010 and demonstrated by Chan et al (2006), planning for ecosystem services can benefit from the two decades of research and development that has gone into the field of conservation planning, a subdiscipline of conservation biology which deals with identifying spatial priorities for conservation actions. Systematic conservation planning (SCP) has already been used extensively around the world to plan for biodiversity (Margules and Pressey, 2000;Sarkar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted in Egoh et al (2007Egoh et al ( , 2010 and demonstrated by Chan et al (2006), planning for ecosystem services can benefit from the two decades of research and development that has gone into the field of conservation planning, a subdiscipline of conservation biology which deals with identifying spatial priorities for conservation actions. Systematic conservation planning (SCP) has already been used extensively around the world to plan for biodiversity (Margules and Pressey, 2000;Sarkar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…That review gave additional examples using metaheuristics and other optimization algorithms for forest management. Another rich review of the biodiversity conservation planning tools was (Sarkar et al 2006) and is highly recommended for further reading.…”
Section: Reconfiguration Of Existing Landscape For Nature Conservatiomentioning
confidence: 99%
“…Agricultural systems are nowadays considered as one of the major sources of environmental pollution and deterioration of biodiversity features worldwide, including species extinction (Münier et al 2004;Sarkar et al 2006). However, agroecosystems have the potential to deliver many regulation ecosystem services such as pest regulation, water cleaning, or carbon sequestration.…”
Section: Introductionmentioning
confidence: 99%
“…Although several researchers have developed tools for prioritization of areas under biodiversity criteria (Sarkar et al, 2006), application of these tools to real-world challenges has been rare (see Koleff et al, 2009 for an exception). More recently, however, prioritization thinking has been broadened considerably to include multi-factor, multi-temporal scenarios, which have the potential to cover much more of the true complexity of the challenge (Sarkar et al, 2006).…”
Section: Synthetic Conservation Planningmentioning
confidence: 99%